Kansas, the Flint Hills, and Water - Susan Stover (Symphony in the Flint Hills, 2014)
Water has carved the distinctive rolling landscape of the Flint Hills, with its limestone ledges and hilltops thick with chert gravel. Water has also shaped how people have settled across Kansas and made use of the land. Early travelers followed the rivers. Prior to the railroad the Arkansas and Kansas Rivers served to transport people and goods.
Keywords: water; flint hills; sunset; chert; landscape; natural; people; transport; Platte River; Ogallala High Plains; aquifer; Water Resources; stream; lake; pond; fish; fishing; drought; Minimum Desirable Streamflow(MDS); ground; Chapman Creek; Dickinson County; Walnut River; Winfield; Whitewater River; Towanda; Tuttle Creek; Milford; reservoir; watershed; floods; travelers